Politically Feasible Reforms of Nonlinear Tax Systems - Bierbrauer, Felix J.; Boyer, Pierre C.; Peichl, Andreas (American Economic Review, 2021)
We study reforms of nonlinear income tax systems from a political economy perspective. We present a median voter theorem for monotonic tax reforms, reforms so that the change in the tax burden is a monotonic function of income. We also provide an empirical analysis of tax reforms, with a focus on the United States. We show that past reforms have, by and large, been monotonic. We also show that support by the median voter was aligned with majority support in the population. Finally, we develop sufficient statistics that enable to test whether a given tax system admits a politically feasible reform. (JEL D72, H21, H24)